The Trend of CRISPR‑Based Technologies in COVID‑19 Disease: Beyond Genome Editing - Najafabadi, Zeinab Yousefi; Fanuel, Songwe; Falak, Reza; Kaboli, Saeed; Kardar, Gholam Ali (Springer, 2022)
Biotechnological approaches have always sought to utilize novel and efficient methods in the prevention, diagnosis, and treatment of diseases. This science has consistently tried to revolutionize medical science by employing state-of-the-art technologies in genomic and proteomic engineering. CRISPR–Cas system is one of the emerging techniques in the field of biotechnology. To date, the CRISPR–Cas system has been extensively applied in gene editing, targeting genomic sequences for diagnosis, treatment of diseases through genomic manipulation, and in creating animal models for preclinical researches. With the emergence of the COVID-19 pandemic in 2019, there is need for the development and modification of novel tools such as the CRISPR–Cas system for use in diagnostic emergencies. This system can compete with other existing biotech- nological methods in accuracy, precision, and wide performance that could guarantee its future in these conditions. In this article, we review the various platforms of the CRISPR–Cas system meant for SARS-CoV-2 diagnosis, anti-viral therapeutic procedures, producing animal models for preclinical studies, and genome-wide screening studies toward drug and vaccine development.